POPULAR PIETY AND LITURGICAL INCULTURATION IN THE PHILIPPINES: THE WEDDING OF FAITH AND CULTURE - Asis, Michael Demetrius H. (Asian Horizons, 2014)
In the Philippines, the concrete outcome of the interaction between the Catholic Faith and culture is the performance of the rites of popular piety. Most of these rites focus on devotions to Christ, Mary, and the saints. Properly guided, these rites may contribute to a more dynamic, active, participative liturgical worship in the Church — an ideal envisaged by the Constitution on the Liturgy of the Second Vatican Council. While the rites of popular piety engender virtues such as hope, a sense of the Cross in daily life, and fortitude, much can be done so that: 1) they do not degenerate into superstitious and magical forms of worship, and 2) they may be developed into potential vehicles for social and structural change.